Factors Influencing Consumer Behaviour: A Case of McDonald’s - A.A. Gde Satia Utama; Navaneetha Kumar; Sam Jing Wen; Daisy Mui Hung Kee; Tan Min Er; Tan Pei Xin; Yeoh Jun Yuan; Mohideen Hasifa A; Vaishnavi Yadav; Rajesh Kumar Nair; Wulan Ruhiyyih Khanum; Kshitij Shukla; Varsha Ganatra (Global Academia Publisher, 2020)
The purpose of this research is to examine the elements that affect the behaviour of consumer in the fast-food industry (McDonald’s). It also aims to investigate how McDonald’s responds to alter environment and consumer behaviour. The effective recommendation will give after carried out the research. This is relevant to research on such topic as obesity and other health associated problems that currently facing have attracted public attention. As a global fast-food company, McDonald’s has a strong vision of being the best fast-service dining experience in the world fast-food industry. Being the best means offering superior value of product and service in good quantity and quality so that every consumer satisfied with McDonald’s. McDonald’s believe that job satisfaction and motivation are one of the contributing factors to consumer behaviour of McDonald’s. A quantitative approach was adopted and self-administered questionnaire survey was distributed to collect data from the consumer.